PENGETAHUAN PETANI KENTANG TERHADAP PROSEDUR PEMBIAYAAN SYARIAH DI KECAMATAN PASIRWANGI, KABUPATEN GARUT - Deviawati Deviawati; Eliana Wulandari (Universitas Galuh Ciamis, 2021)
Pasirwangi subdistrict is one of the potato producing centers in Garut District. In carrying out the farming, farmers have faced various problems, one of which is capital. This is because farming potatoes requires a relatively large cost, so it requires financing other than private capital. The purpose of this study was to analyze the knowledge of potato farmers on the procedure to obtain sharia finance and factors related to the knowledge. This research used quantitative methods. Data were collected from 50 potato farmers in the Pasirwangi Subdistrict, Garut District. The data analysis method used gap analysis and ordinary least square. The result of this study shows that the farmers lacked knowledge on the procedure to obtain sharia finance. That was because most the farmers thought that sharia financing was similar with conventional financing, most farmers’ education level were primary school and their experience in accessing financing was mostly from middlemen. Factors that had a significant influence on the procedure to obtain sharia finance were income, experience of accessing finance, sources of information, and gender.